2010
DOI: 10.1371/journal.pone.0008697
|View full text |Cite
|
Sign up to set email alerts
|

Role for DNA Methylation in the Regulation of miR-200c and miR-141 Expression in Normal and Cancer Cells

Abstract: BackgroundThe microRNA-200 family participates in the maintenance of an epithelial phenotype and loss of its expression can result in epithelial to mesenchymal transition (EMT). Furthermore, the loss of expression of miR-200 family members is linked to an aggressive cancer phenotype. Regulation of the miR-200 family expression in normal and cancer cells is not fully understood.Methodology/Principal FindingsEpigenetic mechanisms participate in the control of miR-200c and miR-141 expression in both normal and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
214
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(236 citation statements)
references
References 44 publications
21
214
0
1
Order By: Relevance
“…DNA hypermethylation has been found to be associated with miR-200 family silencing in breast cancer (28). We find that treatment with epigenetic therapy (the HDAC inhibitor SAHA) can lead to re-expression of miR-200a in breast cancer cells.…”
Section: Discussionmentioning
confidence: 71%
“…DNA hypermethylation has been found to be associated with miR-200 family silencing in breast cancer (28). We find that treatment with epigenetic therapy (the HDAC inhibitor SAHA) can lead to re-expression of miR-200a in breast cancer cells.…”
Section: Discussionmentioning
confidence: 71%
“…Recent studies showed that epigenetic mechanisms are involved in the regulation of miR-200 expression (Vrba et al, 2010;Wiklund et al, 2010) Two recent papers reported that miR-200b is involved in angiogenesis. As stated earlier, miR-200b targets Ets-1 and inhibits angiogenic activity of HMECs (Chan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that miR-200 family members were downregulated in many tumors, including breast, pancreatic and bladder cancers because of hypermethylation of the miR-200 promoter Neves et al, 2010;Vrba et al, 2010;Wiklund et al, 2011). To test whether the downregulation of miR-200 family members in SNU484-LPCX cells resulted from miR-200 promoter hypermethylation, we treated SNU484-LPCX cells with 5-aza-2 0 -deoxycytidine.…”
Section: Regulation Of the Mir-200 Promoter By Smad3mentioning
confidence: 99%